THE CONCEPT OF DIGITAL-BASED MILITARY LOGISTICS SUPPLY CHAIN MANAGEMENT: STRENGTHENING ACCURACY AND SPEED AS WELL AS TRANSPARENCY AND ACCOUNTABILITY - Ferry M. Arifin (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2024)
Logistics supply chain management in the military context, especially in the Indonesian Navy, has not fully adopted the Logistics Supply Chain Management system. This paper aims to develop a digital-based military logistics supply chain management concept to strengthen accuracy and speed as well as transparency and accountability in a clear and realizable framework. The research method used is the qualitative descriptive analysis by building a digital-based military logistics supply chain management concept based on an in-depth analysis of reliable factors and strategies. This research produced findings in the form of a digital-based military logistics concept with significant factors, namely technology, and infrastructure, trained human resources, standardized processes, security and privacy, as well as effective collaboration and communication, all of which contribute to increasing accuracy, speed, transparency, and accountability. The final result of this research is to obtain strategies that include applying advanced technology, human resource development, process standardization, and collaboration between internal and external parties. By adopting these strategies, digital-based military logistics supply chain management can increase accuracy, speed, transparency, and accountability, strengthening operational readiness and overall military mission effectiveness.